Controle da Leptospirose em bovinos de leite com vacina autóctone em Santo Antônio do Monte, MG, 2007/2010 - Denise Chiareli (2011)
An outbreak of leptospirosis in dairy cattle was observed in Santo Antônio do Monte, Minas Gerais. The herd had positive reactions in anti-Leptospira hardjo microagglutination test (MAT) and had been previously vaccinated with an experimental vaccine containing serovar hardjo. The MAT revealed 48.06% of cattle positive for serovar hardjo genotype hardjobovis and 36.82% for serovar hardjo genotype hardjoprajitno. The animals had abortions and mastitis withblood in milk. Was isolated leptospira from the urine of two cows with signs suggestive of the disease. It was produced a bacterin with the two strains. The vaccination schedule consisted of two doses of 45 days and revaccination every six months. The vaccine was administered to allanimals in the herd over the age of four months. The assessment of the progress of the disease after vaccination was performed through the reactions obtained by the MAT, leptospira research in the urine and reproductive and productive performance of the herd. Isolates were identified by serology as belonging to serovar hardjo and serogroup Serjoe. Sequencing of ribosomal 16S region revealed that a sample of isolated belong to the species Leptospira interrogans genotype hardjoprajitno and the second probably belongs to the species L. borgpetersenii hardjobovis genotype. The autochthonous vaccine, combined with the vaccination method used was effective in controlling leptospirosis in cattle in two years. The results showed no positive animals in the last serology in the herd. The reproductive and productive performance of the herd showed improvement after the introduction of vaccination, compared to the previous year, when the disease was diagnosed on the property.